Data quality and trust in big data : 5th International Workshop, QUAT 2018, held in conjunction with WISE 2018, Dubai, UAE, November 12-15, 2018, revised selected papers /: 5th International Workshop, QUAT 2018, held in conjunction with WISE 2018, Dubai, UAE, November 12-15, 2018, revised selected papers. ([2019]) - Unknown
No abstract available